Numerical and experimental investigation of gas flow field variations in three-dimensional printed gas-dynamic virtual nozzles - Nazari, Reza; Ansari, Adil; Herrmann, Marcus; Adrian, Ronald J.; Kirian, Richard A. (Frontiers in Mechanical Engineering, 2023)
Gas-Dynamic Virtual Nozzles (GDVNs) ganan1998generation, wiedorn2018rapid play a vital role in delivering biomolecular samples during diffraction measurements at X-Ray free-electron laser facilities chapman2011femtosecond. Recently, submicrometer-resolution capabilities of two-photon polymerization 3D printing techniques cumpston1999two opened the possibility to quickly fabricate GDVNs nelson2016three, knovska2020ultracompact, nazari20203d with practically any geometry. In our previous work nazari20203d, we exploited this capability to print asymmetric GDVNs that out-performed conventional symmetric designs, which naturally leads to the question of how to identify the optimal GDVN geometry. In this work, we develop a 3D computational fluid dynamics pipeline to investigate how the properties of microjets are affected by GDVN geometry, which will allow for further geometry optimizations and explorations. We used open-source software (OpenFOAM) and an efficient geometric Volume of Fluid method (isoAdvector) scheufler2019accurate to affordably and accurately predict jet properties for different nozzle geometries. Computational resources were minimized by utilizing adaptive mesh refinement. The numerical simulation results showed acceptable agreement with the experimental data, with a relative error of about 10 percent for our test cases that compared bell- and cone-shaped sheath-gas cavities. In these test cases we used relatively low sheath gas flow rate (6 mg/min), but future work including the implementation of compressible flows will enable the investigation of higher flow rates and the study of asymmetric drip-to-jet transitions.